Study of phenolic content and antioxidant activity of Greek red and white wines by means of classical methods and FTIR - Strataridaki, Argiro E. (Cranfield University, 2015)
Phenolic and antioxidant contents of wines are very important in terms of both flavour attributes and health benefits. Changes occur during ageing of wine in containers (e.g. wooden barrels) in relation to their antioxidant activity and phenolic content. Vilana, Dafni, Kotsifali and Mandilari single variety Cretan wines, were vinificated to determine their antioxidant activity and phenolic content Wines were aged in different containers after two vinifications. Changes in the above characteristics were determined every three months for a twelve month period. Stainless steel with and without oenosticks containers, American oak, French oak, Acacia and Chestnut barrels were used for wine ageing. As far as phenolic and antioxidant contents are concerned, ageing of wine in chestnut barrels, Kotsifali and Mandilari (red wines) and in Acacia barrels for Vilana and Dafni (white wines), gave the best results, achieving the highest phenolic content and antioxidant activity after 12 months of ageing. The phenolic fingerprints of Vilana, Dafni, Kotsifali and Mandilari wines were determined for the first time. The phenolic fingerprint of wines has been recently used for the authentication and discrimination of red wines. In this study, attempt has also been made to use the phenolic fingerprint of white wines, for authentication. Differences were observed in Kotsifali and Mandilari (red wines) and in Vilana and Dafni (white wines) directly after vinification, allowing their discrimination. Also the changes in their phenolic fingerprints were monitored during ageing in different containers for a 12 month period. The effect of hydroxytyrosol and oleuropein on wine spoilage induced by acetic acid bacteria was also determined. Hydroxytyrosol was better than oleuropein in controlling the increase of volatile acidity, causing wine spoilage. Wines treated with 0.5mg/l hydroxytyrosol showed control of volatile acid production, and may be a promising alternative to sulphites in wine production in the future. Finally, extracts obtained from olive oil mills and winery by-products were used in Vilana vinification instead of sulphites and antioxidant activity and phenolic content of the wines determined.